STRATEGI BELAJAR MENGAJAR DENGAN MENERAPKAN METODE EKSPERIMEN UNTUK MENINGKATKAN PRESTASI BELAJAR MATA PELAJARAN DASAR LISTRIK DAN ELEKTRONIKA PADA SISWA KELAS X TITL TAHUN PELAJARAN 2019/2020 - Afriadi Afriadi (Ensiklopedia of Journal, 2022)
Abstract: The use of the experimental method is expected to increase student activity in the teaching and learning process so that in the teaching and learning process there is no saturation of teaching and learning activities, thus students will be physically, emotionally and intellectually involved which in turn is expected to understand the concept of learning taught by the teacher. by students. The problems that want to be studied in this research are: (a) How is the improvement of learning achievement in Basic Electrical and Electronics subjects by applying the experimental method? (b) How is the effect of the Experimental method on student achievement? While the objectives of this research are: (a) Want to know the improvement of student achievement after the implementation of the experimental method. (b) Want to know the effect of student learning motivation after the experimental method is applied. This research uses three rounds of action research. Each round consists of four stages, namely: design, activities and observations, reflection, and revision. The target of this research is the students of Class X TITL. The data obtained in the form of formative test results, observation sheets of teaching and learning activities. From the results of the analysis, it was found that student learning achievement increased from cycle I to cycle III, namely, cycle I (47.22%), cycle II (69.44%), cycle III (91.67%). The conclusion of this study is that learning with the experimental method can have a positive effect on achievement and learning motivation of students at SMK Negeri 1 Mandau Kab. Bengkalis, as well as this learning model can be used as an alternative learning in Basic and Electronics subjects.Keywords: Basic Electricity and Electronics, Experimental Method.